KONTRIBUSI KELINCAHAN DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP KEMAMPUAN DRIBBLING PADA PEMAIN BOLA BASKET - Abdul Gafur (Lambung Mangkurat University, 2014)
Contribution to agility and flexible the wrist Against the ability of Dribbling On the country JUNIOR basketball player 1 Kusan Hilir. The purpose of this research is to find out whether or not there are: 1) the contribution towards agility ability dribbling a basketball player basketball JUNIOR Home Affairs 1 Kusan Hilir; 2) wrist kelentukan Contribution to the ability of dribbling on the country JUNIOR basketball player 1 Kusan Hilir; 3) contribution to agility and flexible the wrist together against the ability of dribbling on the country JUNIOR basketball player 1 Kusan Hilir. The methods used in this research is a method of ex post facto. The technique used is to test techniques. The population in this research is the whole basketball player state of SMP 1 Kusan Hilir Prince who follow basketball extracurricular activities that aggregate37 people. Sample as many as 37 people with engineering total sampling.The conclusions of this study are that: 1) there is a contribution towards agility ability dribbling on the country JUNIOR basketball player 1 Kusan Hilir; 2) there is a contribution flexible wrist against dribbling ability in basketball basketball player state of SMP 1 Kusan Hilir; 3) there is a contribution to agility and flexible the wrist together against the ability of dribbling on the country JUNIOR basketball player 1 Kusan Hilir. Key words: agility, flexible wrist, basketball dribbling skills